2008
DOI: 10.2114/jpa2.27.255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cold Acclimation on Antioxidant Status in Cold Acclimated Skaters

Abstract: We investigated whether cold acclimation leads to increased activity of the antioxidant defense enzymes and muscle injury. Comparisons were between short track skaters (nϭ6) and inline skaters (nϭ6) during rest and at submaximal cycling (65% VO 2 max) in cold (ambient temperature: 5Ϯ1°C, relative humidity: 41Ϯ8%) and warm conditions (ambient temperature: 21Ϯ1°C, relative humidity: 35Ϯ5%), during 60 min, respectively, and during the recovery phase. Erythrocyte superoxide dismutase (SOD), catalase (CAT), glutath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
(35 reference statements)
4
8
0
Order By: Relevance
“…In addition, other scenarios may be considered for cold exposureinduced cardiac contractile dysfunction. For example, cold exposure has been reported to promote accumulation of ROS and oxidative stress as well as alteration of antioxidant defense (15,35). This is supported by our findings of overt oxidative stress in cold-challenge hearts manifested as ROS accumulation, carbonyl formation, and reduced GSH/GSSG ratio.…”
Section: E82supporting
confidence: 89%
See 1 more Smart Citation
“…In addition, other scenarios may be considered for cold exposureinduced cardiac contractile dysfunction. For example, cold exposure has been reported to promote accumulation of ROS and oxidative stress as well as alteration of antioxidant defense (15,35). This is supported by our findings of overt oxidative stress in cold-challenge hearts manifested as ROS accumulation, carbonyl formation, and reduced GSH/GSSG ratio.…”
Section: E82supporting
confidence: 89%
“…Moreover, cold exposure seems to prompt much more pronounced cardiovascular sequelae in individuals with preexisting cardiovascular and respiratory illnesses (4,17). Although a number of theories have been postulated for cold exposure-induced cardiovascular anomalies, including overactivation of endothelin-1 cascade, oxidative stress, and compromised antioxidant defense following cold stress (15,26,35), the ultimate culprit factor and effective therapeutic remedy against cold exposureinduced cardiovascular comorbidities remain elusive. Recent evidence from our laboratory revealed that cold exposure elicited cardiac geometric and contractile anomalies accompanied with overt oxidative stress, loss of mitochondrial biogenesis, and oxidative phosphorylation, the effects of which were alleviated significantly by knockout of endothelin-1 receptor (ET A ) (35).…”
mentioning
confidence: 99%
“…Therefore, it seems that the most important element in this antioxidant system is the ability to quickly regain the reduced glutathione rather than the total glutathione concentration. This is supported by other studies, which have shown that the total glutathione concentration is not affected by several conditions causing oxidative stress to the muscle fibers [31], whilst cold acclimation can even cause reduction in the total glutathione concentration [32]. On the contrary, exposure to low temperatures [33], hypoxia [34], high altitude [35], exercise [29], and aging [36] are followed by an increase in glutathione peroxidase or glutathione reductase activity in skeletal muscles.…”
Section: Discussionsupporting
confidence: 67%
“…walking to class, driving to work) in the cold. This dichotomy of distinguishing cold acclimatization status has been used in a previous report using men of similar age and fitness (Hong et al 2008). …”
Section: Subjectsmentioning
confidence: 99%